STRATEGI PENGEMBANGAN PEMASARAN BERAS ORGANIK DI VIGUR ORGANIK CEMOROKANDANG MALANG - Zamrodah, Yuhanin; Dewi Oryza Sativa, Rima; Moelia Moeis, Edya (Universitas Islam Balitar, 2023)
Rice is a basic need of society that must be met. With increasing awareness of a healthy lifestyle, many people are switching from non-organik rice to organik rice for various other reasons. The aim of this research is to determine the marketing development strategy for organik rice in Vigur Organic Cemorokandang, Malang City. The data collection method uses primary and secondary data, while the data analysis method used in this research is the SWOT analysis method. The results of this research show that the SWOT analysis of Vigur Organic in Cemorokandang, Malang City has the highest score of 3.72 which is in the first quadrant, which means it supports the strength - opportunity (SO) strategy. This strategy is a strategy that utilizes strengths in order to obtain as many opportunities as possible in carrying out marketing strategies. Strength - opportunity (SO) strategy by expanding the partnership or cooperation network and expanding marketing reach by utilizing advances in information technology for promotions so as to increase sales of organik rice branded VI-O Organic. The second highest strategy with a score of 3.14 is in the third quadrant, namely weakness-threats (W-T) by maintaining the good quality of organik rice and including a halal logo to maintain safety, which is expected to increase consumer loyalty from competitors.